Breeding biology and hatching success of Chelonia mydas (Testudines: Cheloniidae) in Aves Island Wildlife Refuge, Venezuela, during the 2010 reproductive season - Prieto-Torres, David A. (2015)
Aves Island Wildlife Refuge is the second most important nesting colony for green turtles (Chelonia mydas) in the Caribbean. Even though some research projects have led to a solid source of knowledge about this species’ ecology, little information about its breeding biology is available. This study was focused on assessing the breeding characteristics and hatching success for the nesting population during the 2010 season in Aves Island, Venezuela. Nesting data were collected along the entire beach line from July 31st to November 09th by nightly patrols, in order to determine green turtle nesting activity. All females were tagged and measured to compare the new recruits with remigrant females. We determined the number of nesting females, the size and spatial distribution of clutches, the incubation period, the internesting and remigration periods, as well as the hatching and emergence success for first time in Aves Island. Beach dimensions were measured to determine nest density. We recorded 1 106 nesting females with 436 remigrant females individually identified. The female population had an average curved carapace length of 112.2 ± 5.5 cm. The average clutch size was of 124 ± 25.7 eggs, with an estimated clutch frequency of 2 nests/females, and an average inferred clutch period of 12.4 days. We estimated the total number of clutches to be 2 261 ± 33 and a total of 1 130 ± 17 nesting females for the 2010 season. For in situ nests, we observed a Mean hatching and emergence success of 54.4 ± 30.0% and 74.3 ± 29.2%, respectively. There was a positive correlation between the morphometrics of nesting females and clutch size, and also significant differences in the number of clutches and hatching and emergence success among the different island sections of the study site. Our results are only a first attempt at characterizing this site population, but have great value for establishing conservation priorities within the context of national management plans. Care should be taken in extrapolating our data to other years, as there is a need to continue monitoring the nesting beach and developing conservation strategies directed at all life-stages of the population.